KESEHATAN MENTAL DAN FISIK KELOMPOK RENTAN DI LAPAS: TANTANGAN DAN STRATEGI PENANGANAN - Subroto, Mitro; Afdhallah, Edwin (Ensiklopedia Sosial Review, 2024)
Prisoners in correctional institutions (prisons) are a vulnerable group facing various challenges related to mental and physical health. This study aims to analyze the mental and physical health conditions of vulnerable groups in prisons and their management strategies. The research method used is a literature study by collecting data from various sources such as scientific journals, research reports, and related articles. The results show that prisoners have a higher prevalence of mental disorders and physical illnesses compared to the general population. Contributing factors include overcrowding, exposure to stress, and limited access to health services. Recommended management strategies include increasing the availability and quality of mental and physical health services in prisons, training prison staff on health issues, and coordinating with community health services to ensure continuity of care. Commitment and collaboration from various parties are needed to ensure the fulfillment of prisoners' right to health and promote healthy social reintegration.Keywords: Mental health; physical health; vulnerable groups; correctional institutions; management strategies.